Conservative treatment of esophageal perforation related to a peptic ulcer with pyloric stenosis - Tanaka, Ryo; Kosugi, Shin-ichi; Sato, Daisuke; Hirukawa, Hiroshi; Tada, Tetsuya; Ichikawa, Hiroshi; Hanyu, Takaaki; Ishikawa, Takashi; Kobayashi, Takashi; Wakai, Toshifumi (Clinical journal of gastroenterology, 2014)
We report a case of esophageal perforation (Boerhaave syndrome) caused by vomiting related to a duodenal ulcer with pyloric stenosis. A 45-year-old male presented with left chest pain and dyspnea after forceful vomiting. Chest radiography and computed tomography (CT) revealed a massive left pleural effusion and left tension pneumothorax. Abdominal CT revealed pyloric stenosis with a remarkably dilated stomach. Tube thoracostomy and nasogastric suction were immediately performed and we selected conservative treatment based on the following factors—a stable general condition without sepsis, early diagnosis, and good drainage. Esophagogastroduodenoscopy on hospital day 9 demonstrated a healing ulcer in the lower esophagus and pyloric stenosis. We performed distal gastrectomy as elective surgery for pyloric stenosis due to a duodenal ulcer on hospital day 30. In summary, an esophageal perforation with contamination spreading to the thoracic cavity was successfully treated with conservative treatment.